The impact of housing payment problems on health status during economic recession: A comparative analysis of longitudinal EU SILC data of 27 European states, 2008–2010. (December 2016) - Clair, Amy; Loopstra, Rachel; Reeves, Aaron; McKee, Martin; Dorling, Danny; Stuckler, David
Abstract: Although the recent Great Recession had its origins in the housing sector, the short-term health impact of the housing crisis is not well understood. We used longitudinal data to evaluate the impact of housing payment problems on health status among home-owners and renters in 27 European states. Multi-level and fixed-effects models were applied to a retrospective cohort drawn from the EU Statistics on Income and Living Conditions survey of employed persons, comprising those without housing arrears in the base year 2008 and followed through to 2010 ( n =45, 457 persons, 136, 371 person-years). Multi-variate models tested the impact of transitioning into housing payment arrears on self-reported health (0-worst to 4-best), adjusting for confounders including age, sex, baseline health, and individual fixed effects. Transitioning into housing arrears was associated with a significant deterioration in the health of renters (−0.09 units, 95% CI −0.05 to −0.13), but not owners (0.00, 95% CI −0.05 to 0.06), after adjusting for individual fixed effects. This effect was independent of and greater than the impact of job loss for the full sample (−0.05, 95% CI −0.002 to −0.09). The magnitude of this association varied across countries; the largest adverse associations were observed for renters in Belgium, Austria, and Italy. There was no observed protective association of differing categories of social protection or of the housing regulatory structure for renters. Women aged 30 and over who rented appeared to have worse self-reported health when transitioning into arrears than other groups. Renters also fared worse in those countries where house prices were escalating. We therefore find that housing payment problems are a significant risk factor for worse-self reported health in persons who are renting their homes. Future research is needed to understand potential sources of health resilience among renters, especially at a time when housing prices are rising in many European states. Highlights: Falling into housing arrears is detrimental to health for renters, but not owners. The impact of housing arrears on health varies considerably across countries. Similarly, tenure differences in health vary across European countries. The health of home owners in Poland suffers considerably if they fall into arrears. House price increases exacerbate health effects.